Analisis Penerapan Hukum Waris Adat dan Hukum Waris Islam di Masyarakat Seberang Kota Jambi - Sri Hayani; Zainal Arifin Hoesein; Fauziah Fauziah (Jurnal Hukum Jurisdictie, 2021)
Regulations regarding inheritance in Indonesia still have pluralism, namely Islamic inheritance law and civil inheritance law. Civil inheritance law is further divided into civil inheritance law which is subject to the Civil Code and civil inheritance law which is subject to customary inheritance law (sourced from customary law which is different in each region). The diversity in the law cannot be found from the classifications in society that have been carried out since the colonial era. The division of the Indonesian population is based on Article 131 IS and Article 163 IS. (Indische Staats Regeling). The Jambi City Seberang community is one of the Jambi city community communities whose population is predominantly Muslim. In distributing inheritance they have various guidelines, some are guided by Islamic inheritance law, some are guided by customary inheritance law. However, the majority of the people prefer customary inheritance law. However, in practice the implementation of inheritance distribution uses Islamic inheritance law, customary inheritance law and grants. The objectives of this study are: 1. To find out the mechanism for the distribution of inheritance in the Seberang City Jambi community 2. To find out the application of the law in the Seberang Jambi City community in obtaining legal certainty. This research uses qualitative research, the type of research is case study, data collection is done by interview, field observation, and documentation. After the data is obtained, then it is analyzed and the results can open the mechanism of inheritance distribution in communities across the city of Jambi, namely: determining the distribution of inheritance if a single husband and wife and more than one wife, then separating the inheritance into 3 parts, namely heavy assets, light assets and Seko, secondly, the application of the law of inheritance distribution across the city of Jambi is that all heirs divide their inheritance by combining customary inheritance law and Islamic inheritance law based on the belief that they have implemented customary law that they have had for generations but not leave Islamic inheritance law as the basis for the beliefs they profess and believe in. All research results are in written form that is neatly arranged and detailed.